Atomization of silver nanoparticles suspension as an alternative for generating nanosilver aerosol - Rosa Paula de Freitas; Martins Jaqueline Costa; Lima Bruno de Araújo; Oishi Marcos Vinícius Camargo; Aguiar Mônica Lopes; Bernardo André (Chemical Industry and Chemical Engineering Quarterly, 2018)
Nanomaterials are highly attractive for use in many applications, primarily due to their greater contact surface area and enhanced effects compared to the corresponding bulk materials. However, nanomaterials present risks to human health, since they are able to penetrate deep into the respiratory tract. It is therefore important to know the particle sizes of these substances, although such measurements can present difficulties associated with the generation of this type of material. It is also important to investigate the mechanism of aerosol generation, considering the properties of the starting material. Here, evaluation was performed of the generation of an aerosol of silver nanoparticles from a suspension, using an environmentally friendly and simple synthesis method. A reduction reaction was used to produce the silver nanoparticles. The aerosol was generated using a modified nebulizer inhaler, and particles were counted using an SMPS system. The measurements showed that the predominant particle sizes were 45.63±2.49 nm (determined by SMPS) and 50.7±0.7 nm (determined by DLS analysis).